COST ACCOUNTING VERSUS THE PRICING SYSTEM. - Lawrence, W. B. (The Accounting Review, 1945)
Abstract The article presents a discussion of cost accounting, the pricing system, and the management factor. It preaches to the conclusion that the cost accounting has an important position in these activities. At the same time, it is not all-important. Judgment and discretion in the use of cost data are necessary to deal successfully with the pricing system. The pricing system itself is in some respects a fetish, especially under the conditions that industry is about to encounter. The ability of management to adapt itself to the conditions it meets and to use its ingenuity and resourcefulness in operating under those conditions leads to the most prosperous and profitable results. In the exercise of that ability of management, cost accounting furnishes data that if used wisely and judiciously, greatly expand the opportunities of the manager. Cost accounting at best can be only a tool of management. The skill with which the tool is used is the deciding factor in dealing with pricing situations. It is the man in management that is the truly important factor.